Respostas
respondido por:
1
a)
= (a + 2).(a - 2). (a + 2)
= (a² - 2a + 2a - 2.2).(a + 2)
= (a² - 4).(a + 2)
= a³ + 2a² - 4a - 8
--------------------------------------------------------
b)
= (a + 3). ( a - 3). (a + 3)
= (a² - 3a + 3a - 3.3).(a + 3)
= (a² - 9).(a + 3)
= a³ + 3a² - 9a - 27
= (a + 2).(a - 2). (a + 2)
= (a² - 2a + 2a - 2.2).(a + 2)
= (a² - 4).(a + 2)
= a³ + 2a² - 4a - 8
--------------------------------------------------------
b)
= (a + 3). ( a - 3). (a + 3)
= (a² - 3a + 3a - 3.3).(a + 3)
= (a² - 9).(a + 3)
= a³ + 3a² - 9a - 27
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás